AEg̅IS latest results - Guatieri F.; Aghion S.; Amsler C.; Angela G.; Bonomi G.; Brusa R.S.; Caccia M.; Caravita R.; Castelli F.; Cerchiari G.; Comparat D.; Consolati G.; et al. (EPJ Web of Conferences, 2018)
The validity of the Weak Equivalence Principle (WEP) as predicted by General Relativity has been tested up to astounding precision using ordinary matter. The lack hitherto of a stable source of a probe being at the same time electrically neutral, cold and stable enough to be measured has prevented highaccuracy testing of the WEP on anti-matter. The AEg̅IS (Antimatter Experiment: Gravity, Interferometry, Spectroscopy) experiment located at CERN's AD (Antiproton Decelerator) facility aims at producing such a probe in the form of a pulsed beam of cold anti-hydrogen, and at measuring by means of a moiré deflectometer the gravitational force that Earth's mass exerts on it. Low temperature and abundance of the H̅ are paramount to attain a high precision measurement. A technique employing a charge-exchange reaction between antiprotons coming from the AD and excited positronium atoms is being developed at AEg̅IS and will be presented hereafter, alongside an overview of the experimental apparatus and the current status of the experiment